2015
DOI: 10.12659/msmbr.893827
|View full text |Cite
|
Sign up to set email alerts
|

Heroin Activates ATF3 and CytC via c-Jun N-Terminal Kinase Pathways to Mediate Neuronal Apoptosis

Abstract: BackgroundDrug abuse and addiction has become a major public health problem that impacts all societies. The use of heroin may cause spongiform leukoencephalopathy (SLE).Material/MethodsCerebellar granule cells were derived from 7-day-old Sprague-Dawley rat pups.Neurons were dissociated from freshly dissected cerebella by mechanical disruption in the presence of 0.125% trypsin and DNaseI and then seeded at a density of 4×106 cells/ml in Dulbecco’s modified Eagle’s medium/nutrient mixture F-12 ham’s containing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…All of the genes upregulated in response to SEC have potential links with apoptosis. ATF3 has low expression in normal cells and upregulated with stress signals involved in apoptosis [ 39 41 ]. Accumulating studies indicate that ATF3 may work as a master regulator controlling the expression of PPP1R15A [ 29 , 42 ], IL8 [ 30 ] and TRIB3 [ 31 , 32 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the genes upregulated in response to SEC have potential links with apoptosis. ATF3 has low expression in normal cells and upregulated with stress signals involved in apoptosis [ 39 41 ]. Accumulating studies indicate that ATF3 may work as a master regulator controlling the expression of PPP1R15A [ 29 , 42 ], IL8 [ 30 ] and TRIB3 [ 31 , 32 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although some of the infections are due to passing the pathogens among HDPs through shared needles and unprotected sexual behaviors, chronic heroin abuse and addiction may result in permanent neuronal impairment in HDPs. In animal models, increased cerebellar neuronal apoptosis was observed in heroin-addicted rats 6 , 7 , possibly by activating the c-Jun kinase signaling and related pathways 8 , 9 . Mice that exposed to heroin prenatally showed reduced exploration for objects in novel locations indicating alterations in pyramidal neurons 10 .…”
Section: Introductionmentioning
confidence: 99%
“…They control the fundamental cellular processes of growth, proliferation, differentiation, and cell death when activated by environmental stresses and inflammatory stimuli [14,15]. It has been reported that the MAPKs signal pathways also play a critical role in BBR-mediated regulation of virus replication [13,16].…”
Section: Introductionmentioning
confidence: 99%